Choice of contraceptive methods in public and private facilities in rural India - Arupendra Mozumdar; Vandana Gautam; Abhishek Gautam; Arnab Dey; Uttamacharya; Ruhi Saith; Pranita Achyut; Abhishek Kumar; Kumudha Aruldas; Amit Chakraverty; Dinesh Agarwal; Ravi Verma; et al. (BMC, 2019)
Abstract Background Client-centric quality of care (QoC) in family planning (FP) services are imperative for contraceptive method adoption and continuation. Less is known about the choice of contraceptive method in India beyond responses to the three common questions regarding method information, asked in demographic and health surveys. This study argues for appropriate measurement of method choice and assesses its levels and correlates in rural India. Methods A cross-sectional study was conducted with new acceptors of family planning method (N = 454) recruited from public and private health facilities in rural Bihar and Uttar Pradesh, the two most populous states in India. The key quality of care indicator 'method choice' was assessed using four key questions from client-provider interactions that help in making a choice about a particular method: (1) whether the provider asked the client about their preferred method, (2) whether the provider told the client about at least one additional method, (3) whether the client received information without any single method being promoted by the provider, and (4) client's perception about receipt of method choice. The definition of method choice in this study included women who responded "yes" to all four questions in the survey. The relationship between contraceptive communication and receipt of method choice was assessed using logistic regression analyses, after adjusting for socio-demographic characteristics of the respondents. Results Although 62% of clients responded to a global question and reported that they received the method of their choice, only 28% received it based on responses about client-provider interactions. Receipt of the information on side-effects of the selected method (Adjusted Odds Ratio [AOR]: 7.4, 95% Confidence Interval [CI]: 3.96-13.86) and facility readiness to provide a range of contraceptive choice (AOR: 2.67, 95% CI: 1.48-4.83) were significantly associated with receipt of method choice. Conclusions Findings demonstrated that women's choice of contraceptive could be improved in rural India if providers give full information prior to and during the acceptance of a method and if facilities are equipped to provide a range of choice of contraceptive methods.